Optical fiber humidity sensor based on a tapered fiber with hydroxyethylcellulose/polyvinylidenefluoride composite - Lokman, A.; Nodehi, S.; Batumalay, Malathy; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (John Wiley & Sons, 2014)
A simple relative humidity (RH) sensor is demonstrated using a tapered fiber with an hydrogel coating. Hydroxyethylcellulose/polyvinylidenefluoride polymers are used to form the hydrogel coating of the tapered fiber as they are sensitive to moisture and thus the humidity of the atmosphere. Changes in humidity level alter the refractive index of the fiber coating and this condition leads to variation in optical output power. A difference of up to 0.89 dB of the transmitted optical power is observed when RH changes from 50 to 80%. The proposed sensor has a sensitivity of about 0.0228 dB/%RH with a slope linearity of more than 99.91%. In summary, the hydrogel coating acts as an inner cladding whose refractive index decreases with the rise in humidity and thus allows more light to be transmitted in humid state.